2020
DOI: 10.1111/jce.14398
|View full text |Cite
|
Sign up to set email alerts
|

Late clinical outcomes of lambre versus amplatzer occluders for left atrial appendage closure

Abstract: Introduction The LAmbre (LifeTech Scientific, Shenzhen, China) is a novel occluder for left atrial appendage closure (LAAC) in patients with atrial fibrillation. This study compares late clinical outcomes of LAmbre and the established Amplatzer devices (Abbott, St Paul, MN). Methods Between 2012 and 2018, 265 consecutive patients underwent LAAC with LAmbre and Amplatzer devices at a single center. After a 3:1 propensity score matching, 40 (LAmbre) vs 107 (Amplatzer) patients were compared by the primary effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 32 publications
(80 reference statements)
1
23
1
1
Order By: Relevance
“…A comparação entre o LAmbre e o Amplatzer mostrou eficácia em longo prazo e segurança similares em pacientes com FANV. 20,21 Os resultados imediatos e tardios do presente estudo estão de acordo com a literatura disponível. A taxa aceitável das complicações do procedimento e o seguimento favorável desta coorte de pacientes (de alto risco e com condição complexa) é encorajadora.…”
Section: Discussionunclassified
“…A comparação entre o LAmbre e o Amplatzer mostrou eficácia em longo prazo e segurança similares em pacientes com FANV. 20,21 Os resultados imediatos e tardios do presente estudo estão de acordo com a literatura disponível. A taxa aceitável das complicações do procedimento e o seguimento favorável desta coorte de pacientes (de alto risco e com condição complexa) é encorajadora.…”
Section: Discussionunclassified
“…LAA closure with the LAmbre device showed encouraging results in previous studies [ 15 , 18 20 ]. Surprisingly, the small-umbrella LAmbre device was underused in those studies, and there are only a couple of case reports showing its effectiveness [ 21 – 23 ]. In this study, we aimed to evaluate the feasibility, safety, and short-term efficacy of the small-umbrella LAmbre device for occlusion of morphologically complicated LAA in patients with NVAF.…”
Section: Introductionmentioning
confidence: 99%
“…The LAmbre TM occluder was recently introduced to clinical practice and small registry studies have shown high success rates for implantation and acceptable periprocedural complication rates 10‐12 . Data of a combined procedure with the LAmbre device are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] The LAmbre TM occluder was recently introduced to clinical practice and small registry studies have shown high success rates for implantation and acceptable periprocedural complication rates. [10][11][12] Data of a combined procedure with the LAmbre device are still lacking. Different from Amplatzer devices, the umbrella of the LAmbre device has a double stabilization design with eight small distal hooks that engage into the wall of the left atrial appendage (LAA) and eight U-shaped ends trapping in LAA trabeculations (Figure 1).…”
Section: Introductionmentioning
confidence: 99%